The effects of foreign direct investment,external debt and trade openness on economic growth: evidences from ottoman empire 1881-1913 - Lotfi Demikha
The 19th century marked tremendous changes to the Ottoman economy in many ways. The substantial amount was transferred from Europe to the Ottoman Empire in the form of an external loan or foreign investment. More important, substantial amounts were given as a result of the ongoing process of reforms and modernization that the Ottoman Empire engaged attempting to establish a western-style army. Hence, the flow of funds helped the European power to obtain commercial privileges or concessions to undertake a significant investment project. More importantly, the exchange of goods was in favour of imported ones relative to exports, and this was residing mainly on the fact that these European products enjoyed the exemption from taxes. Three main issues are addressed in this thesis. Firstly, the potential macroeconomic determinants for FDI in OE. The second matter is the external debt which is largely relevant to the financial control of European powers who tried to intervene into the domestic affairs. The third key issue is pertained to investigating the influence of foreign direct investment, external debts, and trade openness on the economic growth of Ottoman Empire. The existing literature lacks a comprehensive quantitative analysis of this pattern. Indeed, a great focus was given to the Ottoman Empire history, but minimal attention was directed to the financial performance of the Ottoman economy during the last quarter of the 19th century. Thus, the tales behind the scene remained blur, and the most plausible explanation lies in the book of history, and leaves a vacuum in term of econometric analysis. Therefore, this study is a response to such a shortage in this field. This study utilizes the time-series technique “Autoregressive Distributed Lag Model” (ARDL) on macroeconomic data for the period 1881-1914. The study reveals a significant positive effect of external debt, trade openness, and government expenditure on economic growth. The obtained results also highlight the fact that foreign direct investment and inflation showed a significant negative impact on economic growth. Our findings recommend on focusing on adopting economic policies that promote generating funds using local sources instead of relying on external funders to boost economic development.